2014
DOI: 10.1111/tpj.12404
|View full text |Cite
|
Sign up to set email alerts
|

SIS8, a putative mitogen‐activated protein kinase kinase kinase, regulates sugar‐resistant seedling development in Arabidopsis

Abstract: SUMMARYSugar signaling pathways have been evolutionarily conserved among eukaryotes and are postulated to help regulate plant growth, development and responses to environmental cues. Forward genetic screens have identified sugar signaling or response mutants. Here we report the identification and characterization of Arabidopsis thaliana sugar insensitive8 (sis8) mutants, which display a sugar-resistant seedling development phenotype. Unlike many other sugar insensitive mutants, sis8 mutants exhibit wild-type r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 79 publications
0
26
0
1
Order By: Relevance
“…From studies using various other mutants, signal crosstalk among ABA, sugar, and ethylene in Arabidopsis has been proposed (39), although details of the mechanism have not been clarified. At1g73660, identified as the at6 locus that improves salt-stress tolerance (35), also has been identified as the gene responsible for sugar insensitive8 (sis8) showing sugar-resistant seedling growth (40,41). The loss-offunction mutant of At1g73660, however, exhibited a WT response to ABA, the gibberellic acid biosynthesis inhibitor paclobutrazol, and the ethylene precursor aminocyclopropane carboxylic acid in germination experiments (35,40), indicating that At1g73660 has a distinct function specific to salt and sugar.…”
Section: Discussionmentioning
confidence: 99%
“…From studies using various other mutants, signal crosstalk among ABA, sugar, and ethylene in Arabidopsis has been proposed (39), although details of the mechanism have not been clarified. At1g73660, identified as the at6 locus that improves salt-stress tolerance (35), also has been identified as the gene responsible for sugar insensitive8 (sis8) showing sugar-resistant seedling growth (40,41). The loss-offunction mutant of At1g73660, however, exhibited a WT response to ABA, the gibberellic acid biosynthesis inhibitor paclobutrazol, and the ethylene precursor aminocyclopropane carboxylic acid in germination experiments (35,40), indicating that At1g73660 has a distinct function specific to salt and sugar.…”
Section: Discussionmentioning
confidence: 99%
“…The application of super-resolution fluorescence microscopy (Doksani et al, 2013) will provide dynamic view of regulatory proteins in HXK1-mediated glucose signaling at single-molecule details in different subcellular compartments. It will be interesting to learn whether the E3 ligase, protein kinase and histone acetyltransferase identified through Arabidopsis sugar-response mutants may act downstream or independent of HXK1-mediated glucose signaling (Huang et al, 2010; Heisel et al, 2013: Huang et al, 2013). …”
Section: Direct Glucose Sensing and Signaling Via Hxk1mentioning
confidence: 99%
“…In plants, MAPK cascades have been shown to be involved in signaling pathways and activated by abiotic stresses such as cold, salt, touch, wounding, heat, UV, osmotic shock, and heavy metals (Tena et al, 2001;Zhang et al, 2006;Colcombet and Hirt, 2008;Liu, 2012). Recent studies have suggested that MAPK cascades are involved in several ABA responses, including antioxidant defenses, guard cell signaling, seed germination, and plant growth (Liu and Zhang, 2004;Xing et al, 2008;Jammes et al, 2009;Zong et al, 2009;Wang et al, 2010;Zhang et al, 2010;Huang et al, 2014;Danquah et al, 2015;Lee et al, 2015;Matsuoka et al, 2015). AtMKK1 and AtMPK6 were reported to link each other and mediate ABA-induced H 2 O 2 scavenger CAT1 (catalase 1) gene expression and H 2 O 2 production (Xing et al, 2008).…”
mentioning
confidence: 99%